Supporting Trusted OA Usage Data Reporting And Analytics Through Shared Infrastructure - Joseph, Andrew; Havemann, Jo; Krznarich, Liz; Drummond, Christina (My University, 2023)
This presentation was delivered at Open Repositories 2023 Conference as part of Panel 5: Supporting Trusted OA Usage Data Reporting and Analytics through Shared Infrastructure.
Keywords: Shared Infrastructure; Data; OA Usage